Mapping of Research in the Field of Forest Therapy-Related Issues: A Bibliometric Analysis for 2007–2021 - Wang, Xin; Gong, Xiang-Fei; Xiong, Ke-Xin; Guo, De-Sheng; Liu, Li-Jun; Lin, Chia-Min; Chang, Wei-Yin (Frontiers in Psychology, 2022)
Exposure to forest environments promotes human health. The number of relevant studies in this area has increased rapidly. However, an overall review of relevant analyses from the perspectives of bibliometrics and visualization is lacking. A scientometric analysis of 2545 publications from 2007 to 2021 via the Web of Science database was conducted to identify the knowledge structure and frontiers objectively. The publications were subsequently analyzed in terms of the distribution of journals and countries, citation bursts, major subject areas, and evolutionary stages. The findings showed that the knowledge foundation of forest therapy was multidisciplinary with most published in the fields of environmental sciences and ecology but lacking input from social disciplines. The research hotspots evolved from the early focus on individual benefits obtained from nature to increasing attention on human wellbeing at social-ecological scale. More rigorous experiments with strict randomized controlled trials and blinding are needed to accommodate the trend of forest therapy toward non-pharmacological treatments. According to Shneider’s four-stage theory, forest therapy research is in the third stage of the scientific research process, where more future studies utilizing novel technologies and decision-making frameworks to solve practical issues are needed for introducing health into policies and promoting human well-being.